Scaphopoda (Mollusca) from the Brazilian continental shelf and upper slope (13º to 21ºS) with descriptions of two new species of the genus Cadulus Philippi, 1844 - Caetano, Carlos Henrique Soares; Scarabino, Victor; Absalão, Ricardo Silva (Zootaxa, 2006)
Twenty six species of Scaphopoda, included in 12 genera and five families were identified. Within these, Fustiaria stenoschiza (Pilsbry & Sharp, 1897), Gadila pocula n.comb. (Dall, 1889); G. simpsoni n.comb. (Henderson, 1920) and G. pandionis (Verril & Smith in Verril, 1880) are recorded for the first time for Brazil and two new species of the genus Cadulus are here described. Besides that, six species previously recorded from north and northeast Brazil have their geographical range expanded southward: Antalis circumcincta (Watson, 1879), Episiphon didymum (Watson, 1879), Ep. sowerbyi (Guilding, 1834), Entalina platamodes (Watson, 1879), Gadila dominguensis (Orbigny, 1853) and Compressidens pressum (Pilsbry & Sharp, 1897). In the other hand, Paradentalium infractum n.comb. (Odhner, 1931) has its geographical distribution extended northward to the state of Maranhão (02ºS). Gadila acus (Dall, 1889) is proposed as junior synonym of G. dominguensis (Orbigny, 1853).